Instructor competencies : the standards - Jackson, Kathy L.; Martin, Florence (Professor of learning, design and technology); Ritzhaupt, Albert D., 1980- (IBSTPI book series., 2023)
"The 2021 IBSTPI Instructor Competencies represents the most recent work of the International Board of Standards for Training, Performance and Instruction (IBSTPI). The 2021 IBSTPI Instructor Competencies is a revision of the 2004 competencies and standards, and includes face-to-face, online, and blended settings. The 2021 IBSTPI Instructor Competencies will continue to serve as a guide for individuals and organizations providing educational and training experiences for a wide-range of learners"--